Phylogenetic classification and generic delineation of Calyptosphaeria gen. nov., Lentomitella, Spadicoides and Torrentispora (Sordariomycetes) - Réblová, M. (Stud Mycol, 2018)
The genus Ceratostomella has a long history of taxonomic confusion. While species with evanescent asci have been transferred to the Microascales and Ophiostomatales, the taxonomic status of species with persistent asci has not been completely resolved. In previous studies using DNA sequence data, cultures and morphology, several Ceratostomella spp. were allocated in 13 genera in the Eurotiomycetes and Sordariomycetes. In our study, the systematics of the remaining Ceratostomella spp. with persistent asci is revisited with new collection data, cultures and phylogeny based on novel DNA sequences from six nuclear loci. Bayesian inference and Maximum Likelihood analyses support the monophyly of several wood-inhabiting species formerly classified in Ceratostomella and other unknown morphologically similar taxa and their division into four genera, i.e. Lentomitella, Spadicoides, Torrentispora and the newly described Calyptosphaeria. This robust clade represents the order Xenospadicoidales in the Sordariomycetidae. Comparative analysis of the ITS2 secondary structure revealed a genetic variation among Lentomitella isolates; 11 species were recognised, of which five are newly introduced and two are new combinations. Other taxonomic novelties include four new species and eight new combinations in Calyptosphaeria, Spadicoides, and Torrentispora. Molecular data suggest that Spadicoides is polyphyletic. The core of the genus is positioned in the Xenospadicoidales; Spadicoides s. str. is experimentally linked with sexual morphs for the first time. Based on DNA sequence data, the monotypic genera Xenospadicoides and Pseudodiplococcium are reduced to synonymy under Spadicoides, while Fusoidispora and Pseudoannulatascus are synonymised with Torrentispora. Members of the Xenospadicoidales inhabit decaying wood in terrestrial and freshwater environments and share a few morphological characters such as the absence of stromatic tissue, ascomata with a cylindrical or rostrate neck, similar anatomies of the ascomatal walls, thin-walled unitunicate asci with a non-amyloid apical annulus, disintegrating paraphyses, usually ellipsoidal to fusiform ascospores and holoblastic-denticulate or tretic conidiogenesis. Revised Ceratostomella spp. with persistent asci are listed and the taxonomic status of each species is re-evaluated based on revision of the holotype and other representative material, published details and available phylogenetic data.